Two novel organic–inorganic hybrid materials from tetrachloridometallate(II) salts and 4‐[(E)‐2‐(pyridin‐1‐ium‐2‐yl)ethenyl]pyridinium. Issue 1 (18th December 2014) - Campos‐Gaxiola, José J.; Arredondo Rea, Susana P.; Corral Higuera, Ramón; Höpfl, Herbert; Cruz Enríquez, Adriana
<x xml:space="preserve">Abstract</x> Two organic–inorganic hybrid compounds have been prepared by the combination of the 4‐[(E)‐2‐(pyridin‐1‐ium‐2‐yl)ethenyl]pyridinium cation with perhalometallate anions to give 4‐[(E)‐2‐(pyridin‐1‐ium‐2‐yl)ethenyl]pyridinium tetrachloridocobaltate(II), (C12H12N2)[CoCl4], (I), and 4‐[(E)‐2‐(pyridin‐1‐ium‐2‐yl)ethenyl]pyridinium tetrachloridozincate(II), (C12H12N2)[ZnCl4], (II). The compounds have been structurally characterized by single‐crystal X‐ray diffraction analysis, showing the formation of a three‐dimensional network through X—H...ClnM− (X = C, N+; n = 1, 2; M = CoII, ZnII) hydrogen‐bonding interactions and π–π stacking interactions. The title compounds were also characterized by FT–IR spectroscopy and thermogravimetric analysis (TGA).